A Tree Growing Amidst an OrchestraAutoethnographic Practice in Transformative Learning - David T. Culkin (Adult Education Research Conference, 2015)
How can an adult make meaning from complex transformative learning experiences in order to become a self-authored learner? This autoethnography explores how a male in the general population describes his transformative learning experiences and identity development over 23 years. The author illustrates the value of authoethnographic practice by illustrating how it has promoted his transformation over three decades.
Keywords: autoethnography; transformative learning; identity development